Nurses Burnout, Resilience, and Its Association With Socio-Demographic Factors During COVID-19 Pandemic - Jamebozorgi, Majid Heidari; Karamoozian, Ali; Bardsiri, Tayebe Ilaghinezhad; Sheikhbardsiri, Hojjat (Frontiers in Psychiatry, 2022)
Background In the recent pandemic, nurses have faced workload and being exposed to burnout. Resilience helps address work-related psychological problems such as stressful events and burnout. According to the roles of nurses in the healthcare system, we investigated the relationship between resiliency and burnout in nurses. Material and Methods In this descriptive analytical cross-sectional study, 364 nurses participated from April to June 2021. Census sampling was used to recruit participants. Maslach burnout inventory (MBI), Connor-Davidson Resiliency Scale (CDRISC), and a demographic check-list were utilized to collect data. Data analysis was done using SPSS version 22. Shapiro-Wilk, Kruskal–Wallis test, Mann–Whitney U-test, correlation analysis, and generalized linear model were applied accordingly. Results Overall, the findings showed that nurses had severe symptoms of burnout and a moderate level of resilience. The two domains of burnout, emotional exhaustion and personal accomplishment had a significantly negative correlation with resilience (r = −0.442, p < 0.001 and r = −0.351, p = 0.03, respectively). Linear regression showed that demographic characteristics (Hospital type, ward type, gender, and overtime) were the major predictors of the 3 sub-categories of burnout. A significant negative correlation was observed between burnout and resilience highlighting the role of resilience in reducing burnout (P < 0.05). Conclusion In order to help nurses to tackle and endure burnout in pandemic times, there is a need to implement national and local policies to help them accordingly.